Measurements of Optical Properties of Smoke Particulates Produced from Burning Polymers and Their Implications - Ter-Ki Hong; Beom-Seok Roh; Seul-Hyun Park (Energies, 2020)
A series of cone calorimetry experiments and simultaneous gravimetric sampling and light extinction (GSLE) measurements were performed to determine the optical properties (light obscuration and extinction characteristics) of smoke particulates produced from burning polymers. The polymer selected in the present study was acrylonitrile-butadiene styrene (ABS), which has a moderate smoke yield during combustion, and unplasticized polyvinyl chloride (UPVC), which has a lower smoke yield than ABS. The experiments show that the measured light obscuration for UPVC smoke particles is much lower than that for ABS smoke particles because of the low rate of smoke production during combustion. Results from the simultaneous GSLE measurements demonstrate more clearly that UPVC smoke particles represent a lower efficiency of light obscuration on a per-unit smoke mass basis, resulting in a 41.3% reduction in a mass specific extinction coefficient compared to the ABS smoke particles. Numerical analysis was performed to further elucidate the effect of optical properties on the smoke behavior using the Fire Dynamics Simulator (FDS) (Version 6.7.1, National Institute of Standards and Technology (NIST), Gaithersburg, MD, USA). The numerical results clearly demonstrated that the UPVC combustion, with its relatively low heat release rate and mass specific extinction coefficient, caused a significant delay in detecting a fire with a smoke detector compared to ABS combustion.